Faktor-Faktor Yang Mempengaruhi Praktik Perataan Laba Pada Industri Properti Di Bursa Efek Indonesia - Henny Mulyati (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2015)
This research is to determine the influence of firm size, reputed auditor, ROA, institutional ownership, managerial ownership, net profit margin, financial leverage on income smoothing for property companies listing in Indonesian Stock Exchange. The data used in this study is secondary data by purposive sampling method. The number of samples used are 24 companies using multiple regression analysis. This results showed that partially there are significantly influence between firm size, reputed auditor and managerial ownership. The other variables i.e ROA, managerial ownership, net profit margin, financial leverage are not significantly influence income smoothing.